Hair and Scalp Changes in Cutaneous and Systemic Lupus Erythematosus - Siriorn Udompanich (2019)
© 2018, Springer International Publishing AG, part of Springer Nature. Cutaneous and systemic lupus erythematosus (SLE) commonly involves the hair and scalp. Alopecia can result from direct activity of disease on the scalp or from the state of physical stress in the form of telogen effluvium. Discoid lupus erythematosus and lupus panniculitis/profundus are known to cause scarring alopecia, while accumulation of recent studies has shown that non-scarring alopecia in SLE may have different subtypes, comprising lupus erythematosus-specific and lupus erythematosus-nonspecific changes on histology. This review aims to summarize the clinical pattern, trichoscopic, histopathological, and direct immunofluorescence features of different types of alopecia in cutaneous and systemic lupus erythematosus, as well as exploring their relationship with SLE disease activity.